Salvage radiotherapy for relapsed/refractory non‐Hodgkin lymphoma following CD19 chimeric antigen receptor T-cell (CART) therapy. (March 2023) - Yegya-Raman, Nikhil; Wright, Christopher M.; LaRiviere, Michael J.; Baron, Jonathan A.; Lee, Daniel Y.; Landsburg, Daniel J.; Svoboda, Jakub; Nasta, Sunita D.; Gerson, James N.; Barta, Stefan K.; Chong, Elise A.; Schuster, Stephen J.; et al.
Highlights: Salvage radiotherapy (SRT) for post-CART progression led to excellent in-field response. PFS was better among those with locoregional disease at progression. Post-SRT distant failure was common, highlighting the need for novel systemic agents. Abstract: Background and purpose: CD19-targeting chimeric antigen receptor T-cell (CART) therapy is a promising treatment for relapsed/refractory non-Hodgkin lymphoma, but most patients experience post-CART progression. We describe our institutional experience of salvage radiotherapy (SRT) in this setting. Materials and methods: Of 94 patients who received CART therapy from 2018 to 2020, 21 received SRT for post-CART progression. Patients were divided into two groups: locoregional disease (n = 9 [43 %], all disease encompassable within an RT field) and advanced disease (n = 12 [57 %]). Patterns of failure, progression-free survival (PFS), overall survival (OS), and toxicity were assessed. Results: Median time from CART infusion to SRT was 4.0 months (range, 0.6–11.5 months). In the locoregional disease group, 8/9 patients (89 %) were treated with comprehensive SRT to a median dose of 37.5 Gy in a median of 15 fractions. In the advanced disease group, all patients (n = 12) were treated with focal SRT to a median dose of 20.8 Gy in a median of 5 fractions. Median follow-up post-SRT was 15.2 months. In-field response was observed in 8/9 (89 %) in the locoregional disease and 8/9 (89 %) evaluable patients in the advanced disease groups. 17/18 evaluable patients (94 %) patients experienced post-SRT progression, all with a distant component. Median OS was 7.4 months; 21 months for locoregional disease versus 2.4 months for advanced disease (p = 0.0002). Median PFS was 1.1 month, and similarly poor regardless of group. No grade ≥ 3 toxicities occurred. Conclusions: SRT post-CART therapy appears safe with encouraging in-field response but high rates of out-of-field progression, even for those presenting with locoregional disease, highlighting the need for integration of novel systemic agents.